Investigation of Toxoplasma gondii Seropositivity in Pregnant Women in Kastamonu Province, Turkey - Çalişir, Büşra; Uzel, Ahmet; Kilinç, Çeti̇n; Yaşar Duman, Meli̇ke; Tüfekci̇, Eni̇s Fuat (Galenos Yayinevi, 2022)
Toxoplasma gondii (T. gondii) is a protozoan parasite that infects most warm-blooded animal species and causes toxoplasmosis. Especially infections that occur during pregnancy can lead to serious clinical symptoms. This study retrospectively revealed the T. gondii seroprevalence of pregnant women in Kastamonu province, Turkey.Anti-T. gondii IgM and IgG positivity of 1.294 pregnant women between the ages of 15-44 years who applied to the Obstetrics and Gynecology Outpatients of Kastamonu Training and Research Hospital from January 2018 to January 2022 were investigated retrospectively. The IgG avidity test was performed for both anti-T. gondii IgM and IgG positivity.Anti-T. gondii IgM and IgG seropositivity were determined as 1.1% (n=14) and 20.3% (n=263), respectively. Anti-T. gondii IgM and IgG positivity were detected together in 11 pregnant women. IgG avidity test results of only six pregnant women could be reached, two pregnant had high IgG avidity, and four pregnant had low IgG avidity. Anti-T. gondii IgG positivity rate increased with increasing age (p=0.039).The number of seronegative pregnant women was considered high in Kastamonu. It is significant for expectant mothers to know about prevention methods in order not to acquire toxoplasmosis.
Keywords: igm; seroprevalence; Turkey; toxoplasma gondii; igg; R; Antibodies, Protozoan; Infectious and parasitic diseases; RC109-216; Pregnant People; Immunoglobulin M; Pregnancy; Seroepidemiologic Studies; Immunoglobulin G; Medicine; Humans; Animals; Female; pregnancy; Toxoplasma; Toxoplasmosis; Retrospective Studies